Learning with STEAM Approach for Early Childhood at All Kids Learning House, Madiun City - Prastyaningrum, Ihtiari; Alfina, Alisa; Shella, Geo; Nur Amalina, Fania (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
Early childhood education should ideally adopt an interdisciplinary approach that integrates five fields of study: science, technology, engineering, art, and mathematics. Through the STEAM approach, children can develop various essential life skills, stimulating and encouraging critical thinking and problem-solving abilities. All Kids Learning House is one of the early childhood schools in the city of Madiun. Based on observations and interviews with teachers at the school, it was found that, indirectly, learning activities at All Kids already incorporate the STEAM approach. The challenge lies in designing a cohesive learning activity that involves all five STEAM disciplines. In response to this, the community service team collaborated with the teachers at All Kids to create learning activities that accommodate all five STEAM disciplines. The process involved observation, problem identification, activity planning, conducting socialization and training sessions, implementation, and evaluation. The goal of this initiative is to assess teachers' ability to design learning activities using the STEAM approach. Success parameters for teachers include classroom management skills, the ability to develop worksheets, and student responses. The initiative involved socialization and training sessions for teachers, followed by direct assistance during the teaching and learning process using the STEAM approach. Learning activities included teacher presentations, exploration, and hands-on practice by students. The results of this initiative indicated that the majority of students showed interest in STEAM-based learning activities and demonstrated critical thinking responses to problems contextualized within STEAM.